High-stability uv varnish antioxidant compound and preparation method thereof
Patent Information
- Application Number
- CN202611206306.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]针对现有UV光油抗氧化助剂体系固化抑制、相容性差、易析出、短期抗黄变、储存稳定性差等缺陷,本发明的目的在于提供一种高稳定性UV光油抗氧化复配及其制备方法,旨在实现以下技术目标:
1、抗氧性能更强
Abstract
Description
Technical Field
[0001] This invention relates to the field of UV curable coating additives technology, specifically to a highly stable UV varnish antioxidant compound and its preparation method. Background Technology
[0002] UV curing technology, due to its solvent-free nature, fast curing speed, low energy consumption, and excellent coating performance, has been widely used in wood, plastics, metals, paper, 3C electronics, and other fields, and is a core direction for the green and efficient development of the coating industry. As a core consumable, UV varnish is experiencing continuous market demand growth, and increasingly stringent requirements are being placed on its storage reliability, appearance stability under long-term outdoor use, and mechanical durability.
[0003] The core components of UV varnish include acrylate oligomers, reactive diluent monomers, and photoinitiators. The molecular chains are rich in unsaturated carbon-carbon double bonds, making them highly susceptible to free radical chain oxidation reactions induced by heat, oxygen, and ultraviolet light. During the storage stage, the system self-polymerizes, causing the viscosity to continuously spike, resulting in premature gelation and failure of the varnish and a significantly shortened shelf life. After the coating has cured, it continues to undergo oxidative degradation under the synergistic aging effects of light, heat, and oxygen, leading to defects such as yellowing, gloss reduction, chalking, brittleness, and decreased adhesion.
[0004] Antioxidant additives are key materials for blocking free radical oxidation reactions and improving the storage and weather resistance of UV varnishes. Existing systems are mainly divided into hindered phenols (primary antioxidants), phosphites (auxiliary antioxidants), and hindered amines (light stabilizers). However, the antioxidant capacity of a single additive is limited, and conventional compounding is prone to problems such as compatibility, curing inhibition, and poor weather resistance, which have become key bottlenecks restricting the upgrading of UV varnish performance.
[0005] Currently, most antioxidant protection systems on the market rely on BHT, a hindered phenolic antioxidant (free radical scavenger), to inhibit oxidation reactions. Other systems combine UV absorbers and anti-yellowing agents, such as benzotriazole UV absorbers, with hindered amine free radical scavengers. Although this combination system has achieved some industrial success, it still faces the following technical bottlenecks: (1) BHT focuses on improving short-term resistance to yellowing after curing, but has poor long-term storage stability and weather resistance, and also exhibits precipitation. (2) Problem of delayed UV varnish curing time: Some formulations add UVA (ultraviolet absorber) to prevent yellowing under light sources containing ultraviolet wavelengths after UV curing. As a result, ultraviolet photons are absorbed, leading to insufficient absorption of photoinitiator, a sharp drop in free radical production, and inability to quickly initiate curing; (CRIVELLO JV, REICHMANIS E. PhotopolymerMaterials and Processes for Advanced Technologies[J]. Chemistry of Materials,2014, 26(1): 533-548.). (3) Problem of weakening UV varnish curing strength: In order to reduce yellowing after curing and improve performance, HALS (hindered amine light stabilizers) are also added. The function of this type of molecule is a highly efficient free radical scavenger, which makes the initiating free radical R· generated by the photoinitiator under light irradiation preferentially captured, and at the same time continuously captures chain growth free radicals (P・, POO・), terminating the growth reaction of crosslinking chains, resulting in low crosslinking density and low degree of curing. (Zhang Nanzhe. Study on the inhibitory effect of tertiary amines on oxygen polymerization on the surface of UV-curable adhesives [J]. Fine Petrochemicals, 2005(1): 23-25.); (4) Traditional solid powder hindered phenol and phosphite compound systems have poor compatibility with acrylate systems. They are prone to migration, volatilization and precipitation at high temperatures and during long-term storage, resulting in insufficient long-term antioxidant effect.
[0006] Therefore, there is an urgent need to develop a UV varnish-specific antioxidant compound system that is free of UVA and HALS, does not inhibit UV curing, has excellent compatibility, and provides long-lasting antioxidant and anti-yellowing effects. Summary of the Invention
[0007] To address the shortcomings of existing UV varnish antioxidant additive systems, such as curing inhibition, poor compatibility, easy precipitation, short-term yellowing resistance, and poor storage stability, the present invention aims to provide a highly stable UV varnish antioxidant compound and its preparation method, thereby achieving the following technical objectives: 1. A novel compound antioxidant system containing hindered phenols and phosphorus is provided. This antioxidant system can effectively solve the blooming phenomenon that occurs after prolonged storage due to material compatibility, thereby achieving excellent antioxidant effect. 2. This antioxidant compound system can effectively inhibit the yellowing phenomenon caused by the continued oxidation of photoinitiators containing benzene rings after curing of varnish, which generate quinone compounds. 3. This antioxidant system does not contain UVA or HALS, and will not affect the material's curing time or the mechanical properties after curing.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A highly stable UV varnish antioxidant compound, composed of a primary antioxidant and an auxiliary antioxidant, in parts by weight: 50-80 parts of primary antioxidant and 20-40 parts of auxiliary antioxidant; The primary antioxidant is liquid hindered phenolic antioxidant 1135; the secondary antioxidant is liquid phosphite, selected from at least one of TDP and DPDP; the weight ratio of the primary antioxidant to the secondary antioxidant is (1-4):1.
[0009] On the one hand, this solution uses the primary antioxidant 1135 and the auxiliary antioxidants TDP or DPDP. Both of these antioxidants are liquids, which have better compatibility and dispersibility than traditional powdered antioxidants or powder-liquid combination antioxidants such as antioxidant BHT or the combination of 1135 and 168. They can exert their antioxidant performance more fully during use, solving the problems of poor long-term storage stability and weather resistance, as well as precipitation. On the other hand, hindered phenolic antioxidants can capture free radicals generated by photoinitiators during the photocuring process of varnish, and reduce further oxidation and yellowing during the curing process. At the same time, the phosphite antioxidants can decompose the hydroperoxides generated during thermo-oxidative aging and regenerate the hindered phenolic antioxidants. Therefore, the combined use of hindered phenolic antioxidants and phosphite antioxidants has a synergistic effect, which can significantly improve the anti-yellowing ability of the antioxidant complex. This allows the varnish to maintain color stability and prevent yellowing during photocuring and long-term storage and under light conditions. It also has low volatility and excellent thermal stability, which can effectively prevent the loss of active components under high temperature or long-term storage conditions, improve the overall stability of the antioxidant complex, and make its anti-oxidation and anti-yellowing effects more durable.
[0010] Preferably, the weight ratio of the primary antioxidant to the secondary antioxidant is (2-3):1.
[0011] Preferably, the system does not contain ultraviolet absorber UVA or hindered amine light stabilizer HALS.
[0012] This invention also provides a method for preparing a highly stable UV varnish antioxidant compound, comprising the following steps: S1. Nitrogen purging: Nitrogen gas is introduced into the sealed preparation vessel to replace the air inside the vessel; S2. Feeding and mixing: Add liquid hindered phenol 1135 and liquid phosphite TDP / DPDP according to the formula ratio; S3. Stirring and mixing: Stir at room temperature in a sealed environment for 2 hours to obtain a homogeneous and transparent compound solution; S4. Testing and Filling: After sampling and testing, the product is sealed and filled to obtain the antioxidant compound product.
[0013] This invention also provides a highly stable anti-yellowing UV varnish, comprising a UV varnish substrate and the antioxidant compound described in claim 1, wherein the amount of the antioxidant compound added is 5% of the total mass of the UV varnish substrate; The UV varnish substrate comprises, by weight percentage: 35% polyurethane acrylate oligomer, 56% active monomer, 3% cellulose acetate butyrate leveling agent, and 6% photoinitiator 1173; The active monomer is a compound of trimethylolpropane triacrylate and tripropylene glycol diacrylate in a mass ratio of 49:7; the molecular weight of the polyurethane acrylate oligomer is 4100.
[0014] This invention also provides a method for preparing a highly stable anti-yellowing UV varnish, comprising the following steps: S1. Mix the active monomer and photoinitiator 1173 at a mass ratio of 1:1, stir at 500 rpm for 30 min, heat to 120℃ to dissolve, and cool to obtain mixture A; S2. Mix cellulose acetate butyrate leveling agent and active monomer at a mass ratio of 1:2 and stir at 600 rpm for 30 min to obtain mixture B; S3. Mix polyurethane acrylate oligomer, mixture A, mixture B, and remaining active monomer, stir at 400 rpm for 20 min, and filter through a 200 mesh to obtain a UV varnish substrate. S4. Add 5wt% antioxidant compound to the UV varnish substrate and stir at room temperature for 1 hour to obtain the finished UV varnish.
[0015] The beneficial effects of this invention are: 1. Stronger antioxidant properties Traditional antioxidant compound systems generally use solid hindered phenols as the main antioxidant, combined with light stabilizers and ultraviolet absorbers. This invention replaces this with a combination of liquid hindered phenols and liquid phosphite-based auxiliary antioxidants, which can efficiently and preferentially capture the following free radicals: After the photoinitiator absorbs ultraviolet light and transitions to an excited state, the weak chemical bonds inside the molecule undergo homolytic cleavage, and electrons are evenly distributed to form paired active free radicals. This system can capture the R-free radicals generated in this process in advance, blocking the oxidation chain reaction.
[0016] 2. Excellent compatibility, solving migration and blooming problems. Traditional solutions use a compound system of solid hindered phenols, phosphites, UV absorbers, and / or light stabilizers. However, differences in compatibility exist within the polymer matrix after photocuring, leading to migration, blooming, or volatilization losses with long-term use. This novel liquid antioxidant solution fundamentally eliminates the compatibility problem between materials, significantly improving its long-term stability within the material.
[0017] 3. While addressing yellowing resistance, the curing time remains unaffected. Existing conventional antioxidant complexes require synergistic use with primary antioxidants, UV absorbers, or light stabilizers. If the amount of UV absorber or light stabilizer added to the system is too high, it will passivate the photoinitiator activity and simultaneously capture active free radicals generated during polymerization. This will prolong the overall curing time of the cured material and reduce the degree of polymerization and crosslinking density of the system. This problem leads to two types of defects: first, when the cured coating thickness is too large, the photoinitiator inside the coating cannot be fully excited, making it prone to yellowing under light exposure; second, only the surface layer of the material achieves complete photocuring, while the interior remains incompletely cured, ultimately significantly reducing the overall performance of the cured material. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] The technical solutions of the various embodiments can be combined with each other, but must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by this invention. Example 1
[0020] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 50g hindered phenol 1135, 50g TDP.
[0021] Preparation process: Nitrogen gas is introduced into the preparation vessel, and 1135 and TDP are added into the preparation vessel. The mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex. Example 2
[0022] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 80g hindered phenol 1135, 20g TDP.
[0023] Preparation process: Nitrogen gas is introduced into the preparation vessel, and 1135 and TDP are added into the preparation vessel. The mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex. Example 3
[0024] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 75g hindered phenol 1135, 25g DPDP.
[0025] Preparation process: Nitrogen gas is introduced into the preparation vessel, and 1135 and DPDP are added into the preparation vessel. The mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the analysis, the mixture is filled to obtain the antioxidant complex. Example 4
[0026] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 80g hindered phenol 1135, 20g 168.
[0027] Preparation process: Nitrogen gas is introduced into the preparation vessel, and 1135 and 168 are added into the preparation vessel. The mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the analysis, the mixture is filled to obtain the antioxidant complex. Example 5
[0028] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 66g hindered phenol 1135, 33g TDP.
[0029] Preparation process: Nitrogen gas is introduced into the preparation vessel, and 1135 and TDP are added into the preparation vessel. The mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex. Example 6
[0030] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 75g hindered phenol BHT, 25g DPDP.
[0031] Preparation process: Nitrogen gas is introduced into the preparation vessel, BHT and DPDP are added into the preparation vessel, and the mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex. Example 7
[0032] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 75g hindered phenol 1076, 25g DPDP.
[0033] Preparation process: Nitrogen gas is introduced into the preparation vessel, 1076 and DPDP are added into the preparation vessel, and the mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex. Example 8
[0034] Raw material ratio: Weigh each component precisely according to the following weights and set aside: 75g hindered phenol 1076, 25g TDP.
[0035] Preparation process: Nitrogen gas is introduced into the preparation vessel, 1076 and TDP are added into the preparation vessel, and the mixture is stirred for 2 hours to obtain a mixture. Samples are taken for analysis, and after passing the test, the mixture is filled to obtain the antioxidant complex.
[0036] Yellowing resistance test: UV varnish samples were prepared according to the following method: Based on the total amount of raw materials, the raw material composition of UV varnish, the weight percentage of each component, and the molecular weight of some components are as follows: Oligomer: 35%: Bifunctional polyurethane acrylate oligomer with a molecular weight of 4100; Monomer: 56%: 49% trimethylolpropane triacrylate, 7% tripropylene glycol diacrylate; Leveling agent: 3% cellulose acetate butyrate Photoinitiator: 6% photoinitiator 1173.
[0037] 1) Mix the monomer and photoinitiator in a 1:1 ratio, stir at 500 rpm for about 30 minutes, and heat to about 120°C to fully dissolve the photoinitiator, to obtain mixture A; 2) Mix the leveling agent and monomer in a 1:2 ratio and stir at 600 rpm for about 30 minutes to fully dissolve the leveling agent and obtain mixture B.
[0038] 3) Mix the oligomer, mixture A, mixture B and the remaining monomer, stir at 400 rpm for 20 min, and filter through a 200 mesh screen after stirring to obtain UV varnish.
[0039] Add 5% by weight of different antioxidant formulations to UV varnish and stir at room temperature for 1 hour to obtain the test sample. Comparative Example 1
[0040] Add 5% by weight of BHT to the UV varnish and stir at room temperature for 1 hour to obtain the sample to be tested. Comparative Example 2
[0041] No antioxidants were added to the test sample.
[0042] Performance testing methods 1. Sample preparation: Add 5 wt% of the antioxidant systems of each example and comparative example to the blank UV varnish and stir at room temperature for 1 h; 2. Curing treatment: Take 0.5 mL of sample into a centrifuge tube and expose it to natural light for 30 min for complete curing; 3. Aging test: The cured sample was placed in a 60℃ constant temperature oven for 72 hours for aging; 4. Testing indicators: The yellowing index YI after light exposure and the yellowing index YI after high temperature aging were tested. Visual inspection was conducted to determine whether blooming or precipitation occurred. The results are shown in Table 1.
[0043] Table 1. Antioxidant performance test of antioxidant compound Example 1 0.31 0.29 no Example 2 0.22 0.20 no Example 3 0.11 0.12 no Example 4 0.19 0.19 yes Example 5 0.15 0.16 no Example 6 1.15 1.81 no Example 7 0.81 1.24 no Example 8 0.63 1.15 no Comparative Example 1 1.41 2.4 yes Comparative Example 2 2.33 4.53 no As can be seen from Table 1: 1. Examples 1, 2, 3, and 5 used liquid 1135 combined with liquid TDP / DPDP, with no precipitation and yellowing index much lower than the solid hindered phenol compound system (Examples 6, 7, and 8) and the single BHT comparative example 1; among them, Example 3 (1135 + DPDP) had the best anti-yellowing performance, with yellowing indices at both high and low temperatures below 0.15. 2. In Example 4, when solid 168 phosphite was used, precipitation occurred, proving that the solid phosphite and the liquid hindered phenol have insufficient compatibility and there is a risk of blooming with long-term use. 3. The yellowing index of the solid hindered phenol BHT and 1076 compound system increased significantly, indicating poor resistance to yellowing. BHT alone also showed precipitation defects. 4. The blank sample and comparative example 2 have no antioxidant components, so the oxidation reaction is not inhibited. The yellowing index at high and low temperatures is the highest, and the coating turns yellow severely.
[0044] The above data proves that the antioxidant complex prepared by the present invention using the binary compounding scheme of liquid hindered phenol 1135 + liquid phosphite TDP / DPDP has good anti-yellowing properties and also has certain anti-aging properties at high temperatures. It can simultaneously achieve high compatibility, no precipitation, and ultra-low yellowing index. Moreover, the system does not contain UVA or HALS and does not interfere with the UV curing process. The best formulation of the present invention has very low anti-yellowing indices under light and high temperature, which are 0.11 and 0.12, respectively, improving the anti-yellowing performance by more than 95% without causing the precipitation of antioxidants. When added to UV varnish, it has outstanding anti-yellowing effect and perfectly solves multiple defects of the prior art.
[0045] It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the invention. Furthermore, it should be understood that after reading the technical description of this invention, those skilled in the art can make various alterations, modifications, and / or variations to the invention, and all such equivalent forms also fall within the scope of protection defined by the appended claims.
Claims
1. A highly stable UV varnish antioxidant compound, characterized in that, It consists of a primary antioxidant and a secondary antioxidant, in parts by weight: 50-80 parts primary antioxidant and 20-40 parts secondary antioxidant; The primary antioxidant is liquid hindered phenolic antioxidant 1135; the secondary antioxidant is liquid phosphite, selected from at least one of TDP and DPDP; the weight ratio of the primary antioxidant to the secondary antioxidant is (1-4):
1.
2. The high-stability UV varnish antioxidant compound according to claim 1, characterized in that, The weight ratio of the primary antioxidant to the secondary antioxidant is (2-3):
1.
3. The high-stability UV varnish antioxidant compound according to claim 1, characterized in that, The system does not contain UVA absorber or HALS hindered amine light stabilizer.
4. The preparation method of a high-stability UV varnish antioxidant compound according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Nitrogen purging: Nitrogen gas is introduced into the sealed preparation vessel to replace the air inside the vessel; S2. Feeding and mixing: Add liquid hindered phenol 1135 and liquid phosphite TDP / DPDP according to the formula ratio; S3. Stirring and mixing: Stir at room temperature in a sealed environment for 2 hours to obtain a homogeneous and transparent compound solution; S4. Testing and Filling: After sampling and testing, the product is sealed and filled to obtain the antioxidant compound product.
5. A highly stable anti-yellowing UV varnish, characterized in that, The product comprises a UV varnish substrate and the antioxidant compound of claim 1, wherein the antioxidant compound is added at 5% of the total mass of the UV varnish substrate; The UV varnish substrate comprises, by weight percentage: 35% polyurethane acrylate oligomer, 56% active monomer, 3% cellulose acetate butyrate leveling agent, and 6% photoinitiator 1173; The active monomer is a compound of trimethylolpropane triacrylate and tripropylene glycol diacrylate in a mass ratio of 49:7; the molecular weight of the polyurethane acrylate oligomer is 4100.
6. The method for preparing a highly stable anti-yellowing UV varnish according to claim 5, characterized in that: S1. Mix the active monomer and photoinitiator 1173 at a mass ratio of 1:1, stir at 500 rpm for 30 min, heat to 120℃ to dissolve, and cool to obtain mixture A; S2. Mix cellulose acetate butyrate leveling agent and active monomer at a mass ratio of 1:2 and stir at 600 rpm for 30 min to obtain mixture B; S3. Mix polyurethane acrylate oligomer, mixture A, mixture B, and remaining active monomer, stir at 400 rpm for 20 min, and filter through a 200 mesh to obtain a UV varnish substrate. S4. Add 5wt% antioxidant compound to the UV varnish substrate and stir at room temperature for 1 hour to obtain the finished UV varnish.